Ecological Analysis of Bird Communities at Kawasan Hutan dengan Tujuan Khusus (KHDTK) Muhammadiyah University of Mataram - Gunadi, Putu Eka; Johari, Harry Irawan; Nurhayati, Nurhayati (Jurnal Biologi Tropis, 2025)
Birds have a vital ecological role as pollinators, seed dispersers, and insect population controllers. Their diversity is super important in ecology and conservation studies. This study aims to identify and analyze the bird community structure in the Special Purpose Forest Area of Muhammadiyah University of Mataram. Field surveys were conducted in June 2025 using the point count method at four observation points selected through purposive sampling. Observations were carried out over three time periods with two repetitions at each point. The study recorded 26 bird species from 23 families, totaling 177 individuals. Dominant species included Pycnonotus goiavier, Orthotomus sepium, and Todiramphus chloris. Additionally, endemic species of Nusa Tenggara such as Otus jolandae and Pitta concinna were recorded. Ecological analysis showed a Shannon-Wiener diversity index of 2.99, a Margalef species richness index of 4.83, and an Evenness index of 0.92. These values reflect a stable, healthy bird community with an even distribution of individuals without the dominance of any particular species. Based on these findings, this study recommends strengthening conservation efforts through the preservation of natural vegetation, regular monitoring of bird populations, and further research.